Le Grand-duche de Varsovie vu par un emigre français ou la relation de cet episode politique dans les Memoires de l'abbe Pochard (1806-1815) - Fischer, Jeremie (Poznańskie Studia Teologiczne, 2014)
The article by Jérémie Fischer titled The Grand Duchy of Warsaw as Seen by a French Emigrant or an Account of this Political Development in the „Mémoires” of Fr. Pochard (1806--1815) presents so far unknown threads of political, social and military developments in the period of 1806-1815 connected with the history of the Grand Duchy of Warsaw, of which the French tutor of children from the Skórzewski family was an eye witness. Although the focus of the account contained on the two hundred pages of the diary is largely on the family of Polish landed gentry, due Father Pochard’s many travels and encounters it definitely sheds new light on the historical events pertaining to the history of the Grand Duchy of Warsaw, and thus the diary becomes a valuable source for research on the history of Poland.